2019
DOI: 10.1111/jpn.13210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary l‐carnitine supplementation and energy level on oxidant/antioxidant balance in laying hens subjected to high stocking density

Abstract: This study aimed to investigate the effect of l‐carnitine and energy level and on oxidant/antioxidant balance in laying hens subjected to high stocking density. A total of 176, 32‐week‐old laying hens were assigned to eight groups with four replicates and hens in four groups were placed at the normal stocking densities of 500 cm2/hen (four hens per cage) and in the remaining four groups were placed at the high stocking densities of 287.5 cm2/hen (seven hens per cage). Hens received diets of high (2,850 kcal/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The results obtained in the current study demonstrated that adding the lowest level of LC-SLNs (50 mg/kg) to the diet, significantly improved erythrocyte SOD activity and total antioxidant capacity (T-AOC); which could be attributed to the high bioavailability of LC-SLNs. Previous research found that supplementing with LC increased SOD activity at high stocking density challenged laying hens ( Çetin and Güçlü, 2020 ) and broiler ( Liu et al, 2021 ) which is similar to our findings. These findings suggest that LC plays an important role in antioxidant defense control.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results obtained in the current study demonstrated that adding the lowest level of LC-SLNs (50 mg/kg) to the diet, significantly improved erythrocyte SOD activity and total antioxidant capacity (T-AOC); which could be attributed to the high bioavailability of LC-SLNs. Previous research found that supplementing with LC increased SOD activity at high stocking density challenged laying hens ( Çetin and Güçlü, 2020 ) and broiler ( Liu et al, 2021 ) which is similar to our findings. These findings suggest that LC plays an important role in antioxidant defense control.…”
Section: Discussionsupporting
confidence: 92%
“…We envision that the improvement in villus condition is linked to the increased level of IGF-1. Also, as mentioned earlier, due to the antioxidant properties of LC ( Çetin and Güçlü, 2020 ), it improves antioxidant capacity. We envision that LC may alleviate GPx and SOD depletion as well as lower MDA activity levels in laying hen intestinal tissues.…”
Section: Discussionmentioning
confidence: 65%
“…Long-term intake of high-energy-density feed during breeding will cause peroxidation in livestock and poultry (blood and tissues), and then affect the occurrence and process of inflammation ( 63 65 ). Exogenous antioxidant supplementation in the right amount can enhance the capacity of the antioxidant system in vivo , on the contrary, excessive antioxidants can also disrupt homeostasis ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the use of L-carnitine is gaining attention for its crucial role as a novel antioxidant via preventing DNA damage induced by ROS, stimulating antioxidant enzyme activities, and supporting energy production in laying hens ( Surai, 2015 ; Agarwal et al, 2018 ). Dietary L-carnitine supplementation in poultry decreases malondialdehyde ( MDA ) levels and increases SOD, CAT, and GSH-Px activities under high stocking density stress ( Çetin and Güçlü, 2019 ). In addition, some studies have reported improved egg production, hatchability, antioxidant activity, and offspring quality in laying hens and duck breeders fed L-carnitine ( Salmanzadeh, 2011 ; Wang et al, 2013 ; Awad et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%